Motivasi Lulusan Sarjana Pendidikan dalam Memilih Pekerjaan di Dunia Bimbingan Belajar dan pengaruhnya Terhadap Kinerja - Ulumiyah, Churriyah; Ramly, Amir Tengku (Jurnal Manajemen, 2019)
Every year, the number of bachelor of education in Indonesia is increased. On the other hand, the amount of job vacancy for bachelor of education in schools as teachers is lower because of the number of teachers who retire less. This makes many bachelors of education look at other jobs in the field of non-formal education as tutoring. Motivations that encourage bachelor of education to enter the world of tutoring are the desire to share their knowledge, obtain adequate welfare (salary), the job as a teacher in school that increased, and the competition to graduate as civil servant teachers is increasingly high. Proof of being a good employee in tutoring can be done with performance motivation that supports quality improvement as a human resource.